Clinical impact of vivax malaria: a collection review - Phyo, AP; Dahal, P; Mayxay, M; Ashley, EA (Public Library of Science, 2022)
Background Plasmodium vivax infects an estimated 7 million people every year. Previously, vivax malaria was perceived as a benign condition, particularly when compared to falciparum malaria. Reports of the severe clinical impacts of vivax malaria have been increasing over the last decade. Methods and findings We describe the main clinical impacts of vivax malaria, incorporating a rapid systematic review of severe disease with meta-analysis of data from studies with clearly defined denominators, stratified by hospitalization status. Severe anemia is a serious consequence of relapsing infections in children in endemic areas, in whom vivax malaria causes increased morbidity and mortality and impaired school performance. P. vivax infection in pregnancy is associated with maternal anemia, prematurity, fetal loss, and low birth weight. More than 11,658 patients with severe vivax malaria have been reported since 1929, with 15,954 manifestations of severe malaria, of which only 7,157 (45%) conformed to the World Health Organization (WHO) diagnostic criteria. Out of 423 articles, 311 (74%) were published since 2010. In a random-effects meta-analysis of 85 studies, 68 of which were in hospitalized patients with vivax malaria, we estimated the proportion of patients with WHO-defined severe disease as 0.7% [95% confidence interval (CI) 0.19% to 2.57%] in all patients with vivax malaria and 7.11% [95% CI 4.30% to 11.55%] in hospitalized patients. We estimated the mortality from vivax malaria as 0.01% [95% CI 0.00% to 0.07%] in all patients and 0.56% [95% CI 0.35% to 0.92%] in hospital settings. WHO-defined cerebral, respiratory, and renal severe complications were generally estimated to occur in fewer than 0.5% patients in all included studies. Limitations of this review include the observational nature and small size of most of the studies of severe vivax malaria, high heterogeneity of included studies which were predominantly in hospitalized patients (who were therefore more likely to be severely unwell), and high risk of bias including small study effects. Conclusions Young children and pregnant women are particularly vulnerable to adverse clinical impacts of vivax malaria, and preventing infections and relapse in this groups is a priority. Substantial evidence of severe presentations of vivax malaria has accrued over the last 10 years, but reporting is inconsistent. There are major knowledge gaps, for example, limited understanding of the underlying pathophysiology and the reason for the heterogenous geographical distribution of reported complications. An adapted case definition of severe vivax malaria would facilitate surveillance and future research to better understand this condition.